Outcomes of external septorhinoplasty in a Turkish male population - ÇALIM, ÖMER FARUK; Kilci, Gamze Didem; Baser, Engin; Verim, Aysegul; Calim, ÖMER FARUK; Veyseller, Bayram; Ozturan, Orhan; Altintas, Ahmet; Celik, Mustafa (My University, 2018)
Introduction:The first and one of the most important steps in facial plastic surgery is accurate preoperative facial analysis and recording of data that may help the surgeon to check the outcomes of his/her techniques, promoting a surgeon-s professional development.